CARICOM Fifty-Fifty: Prospects for Ideological Shift from Personal to Popular Sovereignty (2014)
A balance of CARICOM leadership performance through the first 50 years of the organization is presented, focusing on the participation or exclusion of common people in the evolution of the organization and its member states. It is shown that leaderships have been acting as single persons, mainly supported on their individual authority. This behaviour has led to the exclusion of people from the regional integration process since the construction of sovereignty has resulted in the personal sovereignty of political leaders. Limitations and restriction on people mobility within member states, among other issues, have also arisen as a result of this type of leadership in opposition to the declarations of good intentions in this direction. In accordance with the diagnostic, the need of a new agenda pretending to attain the popularisation of the sovereignty of CARICOM is stated as a component to be taken into account in a wide framework in the projection for the next 50 years of the organization. The required agenda should be constructed on the basis of a sovereignty bargain built around some essential features which allow the attainment of a popular sovereignty involving common people and considering simultaneously the regional and national sovereignties.